2006
DOI: 10.1097/01.moh.0000219654.65538.5b
|View full text |Cite
|
Sign up to set email alerts
|

New insights into carrier binding and epithelial uptake of the erythropoietic nutrients cobalamin and folate

Abstract: New data show the structure of cobalamin carriers and reveal novel proteins involved in the epithelial uptake of cobalamin and folate. Genetic abnormalities in three different genes encoding proteins in the epithelial uptake of cobalamin are now known to cause malabsorption of cobalamin and megaloblastic anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 42 publications
(46 reference statements)
0
17
0
1
Order By: Relevance
“…NE, neuroepithelium; OV, otic vesicle; asterisks represent blood vessel. (Christensen and Birn, 2002;Moestrup, 2006;Moestrup and Verroust, 2001). Megalin (Lrp2) is a low-density lipoprotein receptor-related protein that is coexpressed with cubilin in many absorptive epithelia (i.e., neuroepithelium and yolk sac) of developing embryos that binds and internalizes multiple ligands, including the soluble folate binding protein (Folr1) and sonic hedgehog (Shh), among others (Barth and Argraves, 2001;Birn et al, 2002;Christensen and Birn, 2002;Moestrup et al, 1996;Morales et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…NE, neuroepithelium; OV, otic vesicle; asterisks represent blood vessel. (Christensen and Birn, 2002;Moestrup, 2006;Moestrup and Verroust, 2001). Megalin (Lrp2) is a low-density lipoprotein receptor-related protein that is coexpressed with cubilin in many absorptive epithelia (i.e., neuroepithelium and yolk sac) of developing embryos that binds and internalizes multiple ligands, including the soluble folate binding protein (Folr1) and sonic hedgehog (Shh), among others (Barth and Argraves, 2001;Birn et al, 2002;Christensen and Birn, 2002;Moestrup et al, 1996;Morales et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The highest level of TCII-R expression in human tissue is observed in the kidney, whereas lower levels of expression are found in the intestine, liver, and placenta. Another receptor, megalin, is strongly expressed in the kidneys where it mediates reabsorption and storage of holo-TCII (12)(13)(14). It has been suggested that this kidney tubular cobalamin reabsorption is similar in efficacy to the intestinal uptake (15).…”
Section: Introductionmentioning
confidence: 99%
“…RAP inhibits binding of most ligands to megalin (and to cubilin) thus serving as an important tool for the study of megalin and cubilin [36,37]. Megalin and cubilin share more ligands, including albumin, Folate Binding Protein (FBP), vitamin D binding protein (DBP) and haemoglobin [24]. It is possible that in these cases binding to cubilin enhances binding to and endocytosis by megalin but no direct evidence exists.…”
Section: Introductionmentioning
confidence: 99%